Prevalence of myopia and high myopia, and the association with education: Shanghai Child and Adolescent Large-scale Eye Study (SCALE): a cross-sectional study. Issue 12 (23rd December 2021) - He, Xiangui; Sankaridurg, Padmaja; Xiong, Shuyu; Li, Wayne; Naduvilath, Thomas; Lin, Senlin; Weng, Rebecca; Lv, Minzhi; Ma, Yingyan; Lu, Lina; Wang, Jingjing; Zhao, Rong; et al.
Abstract : Objectives: To report on: (a) overall myopia and high myopia prevalence, and (b) the impact of education on the spherical equivalent refractive error in children across Shanghai. Design: Cross-sectional study. Setting: Across all 17 districts of Shanghai. Participants: 910 245 children aged 4–14 years from a school-based survey conducted between 2012 and 2013. Main outcome measures: Data of children with non-cycloplegic autorefraction, visual acuity assessment and questionnaire were analysed (67%, n=6 06 476). Prevalence of myopia (≤−1.0 D) and high myopia (≤−5.0 D) was determined. We used a regression discontinuity design to determine the impact of school entry cut-off date (1 September) by comparing refractive errors at each age, for children born pre-September to post-1 September, and performed a multivariate analysis to explore risk factors associated with myopia. Data analysis was performed in 2017–2018. Results: Prevalence rates of myopia and high myopia were 32.9% (95% CI: 32.8% to 33.1%) and 4.2% (95% CI: 4.1% to 4.2%), respectively. From 6 years of age onwards, children born pre-September were more myopic compared with those born post-1 September (ahead in school by 1 year, discontinuity at 6 years: −0.19 D (95% CI: −0.09 to −0.30 D); 14 years: −0.67 D (95% CI: −0.21 to −1.14 D)). Conclusions: Our findings suggest that myopia is associated with education, that is primarily focused on near-based activities. Efforts to reduce the burden should be directed to public awareness, reform of education and health systems.